Understanding How Canadian Physicians and Public Stakeholders Rationalize MAiD Amid Bill C-7: A Critical Analysis - Matthew, Midori (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Despite its legalization, the ethics of medical assistance in dying (MAiD) remain contentious due to an evolving eligibility criteria goalpost and the subsequent implications for individuals suffering from non-terminal conditions, namely mental illness. Given the expanding availability of MAiD, comparing societal narratives with those of physicians is important to inform the development of health policies and laws that reflect a variety of stakeholder values and concerns. This paper presents a critical qualitative analysis of two types of data: 1) interview responses from Canadian physicians regarding the practice of MAiD, and 2) Canadian digital news media, with the goal of determining areas of convergence and divergence in the narratives of both source types. This analysis captured four overarching themes: 1) autonomy and choice, 2) “dying with dignity” and harm reduction, 3) paternalism and vulnerability, and 4) the medicalization of suffering. In general, while both physicians and other stakeholders express a commitment to the principle of patient autonomy, all parties raised concerns about systemic inequities and the risk of MAiD being used as a proxy for addressing broader social determinants of health.